Age- and sex-specific trends in the incidence of myocardial infarction in Denmark, 2005 to 2021. (April 2022) - Christensen, Daniel Mølager; Strange, Jarl Emanuel; Phelps, Matthew; Schjerning, Anne-Marie; Sehested, Thomas S.G.; Gerds, Thomas; Gislason, Gunnar
Abstract: Background and aims: Few studies have determined whether the declining incidence of myocardial infarction carries into the current decade, and how it is affected by age and sex. We aimed to determine age- and sex-specific changes in myocardial infarction incidence in Denmark from 2005 through 2021. Methods: First-time myocardial infarction admissions in adults aged ≥18 years were identified through Danish nationwide registries. Incidence rates per 100, 000 persons with 95% confidence intervals (CI) were calculated across calendar year, sex, and age groups (≤49, 50–69, 70–84, ≥85 years). We also presented incidence rate ratios (IRR) with 95% CIs for 2019–2021 compared to 2005–2007. Results: From January 1, 2005, through August 4, 2021, there were 116, 481 incident acute myocardial infarctions in approximately 4.5 million Danes aged ≥18 years. Overall incidence rate of myocardial infarction per 100, 000 persons decreased in both sexes from 2005 through 2021 (females: 143 to 80; males: 243 to 174) and across all age groups. The steepest declines in incidence were observed for ages ≥85 years (males: 55%, IRR: 0.45 [0.41–0.49]; females: 58%, IRR: 0.42 [0.39–0.45]) and 70–84 years (males: 46%, IRR: 0.54 [0.52–0.57]; females: 52%, IRR: 0.48 [0.46–0.51]). Rates also declined significantly for ages 50–69 (males: 19%, IRR: 0.81 [0.79–0.84]; females: 17%, IRR: 0.83 [0.78–0.88]) and ≥49 years (males: 30%, IRR: 0.70 [0.64–0.76]; females: 37%, IRR: 0.63 [0.54–0.74]). Conclusions: Declines in the incidence of myocardial infarction continued into the current decade across age groups and sex. However, significantly steeper absolute and relative declines were observed among the oldest age groups (≥70 years). Highlights: Myocardial infarction incidence continues to decline into the current decade. Steeper absolute and relative declines were observed among the elderly. Future studies should determine if more focus on prevention is needed in the young.